Evaluation of Efficiency of Conventional Empirical Antimicrobial Regimen for the Management of Maxillofacial Fascial Space Infection (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Severe life threatening maxillofacial fascial space infection is caused by wide varieties of aerobic and anaerobic micro organisms. Due to injudicious use of broad spectrum antibiotic therapy and development of resistant microorganisms the conventional empirical antimicrobial therapy is now under threat of treatment failure.Objective: To identify the causative microorganisms of maxillofacial fascial space infections and detection of the effectiveness of conventional antimicrobial agents and find out the most effective empirical antimicrobial regimen against them.Materials and Methods: This is a descriptive cross-sectional study which was conducted at the Department of Oral and Maxillofacial Surgery in CMH Dhaka and Dhaka Dental College Hospital from 01 July 2012 to 30 June 2013. The study was designed with total 50 patients of maxillofacial fascial space infections. Pus or inflammatory exudates from all those 50 patients were collected with special aseptic precaution in both aerobic and anaerobic conditions. The specimens were sent to microbiological laboratory as soon as possible for culture and sensitivity test both in aerobic and anaerobic conditions. The particulars of the patient and results of the culture and sensitivity tests were recorded in the data sheet of the individual patient. Finally the data were presented in the frequency tables and graphs and analyzed by using a statistical software package SPSS 10.0 version.Results: As maximum orofacial space infections are caused by mixed microorganisms so it was difficult to treat those by single empirical antibiotic. Even though Clindamycin was found as a single antibiotic to be sensitive in highest 90% (in 45 patients) cases. Other single effective antibiotics were Erythromycin (50%) and Azithromycin (40%).Conclusion: The study reflects very frustrating and alarming situation regarding the antimicrobial agent sensitivity in the treatment of orofacial space infection. Though less frequently used antibiotics like Clindamycin shown highest sensitivity but merely single broad spectrum antibiotic was effective enough. Empirical antimicrobial therapy could be selected by combination of 2 or more broad spectrum antimicrobial agents.Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 47-54